Revitalisasi Potensi Wisata Desa Rowo Gempol melalui Pembangunan Infrastruktur Penunjuk Jalan - Moch Rijalul Amin AZ; Mohammad Zidan Rafsanjani; Wafiq Nur Azizah; Mila Hariani; Arif Rachman Putra; Samsul Arifin; Ella Anastasya Sinambela (Jurnal Kabar Masyarakat, 2025)
The revitalization of Rowo Gempol Village's tourism potential through the development of directional infrastructure aims to improve accessibility and enhance the village's appeal as a tourist destination. The village's natural and cultural tourism potential has not been fully utilized due to the lack of supporting infrastructure, particularly clear and informative directional signs. Through this initiative, the PkM team, in collaboration with the local community, conducted site identification, designed and installed directional signs, and educated residents on the importance of maintaining and utilizing this infrastructure. Active community participation was key to the program's success, which is expected to broaden visitor access and positively impact the local economy. The results of this program indicate that the construction of directional infrastructure not only facilitates tourists in exploring the village but also strengthens Rowo Gempol Village's image as a well-organized tourist destination. Another positive impact is the increased awareness and sense of responsibility among the community in managing the village's tourism potential, along with new economic opportunities arising from the growth in tourist visits. This initiative successfully achieved its objectives and serves as a model that can be implemented in other villages with tourism potential hindered by inadequate supporting infrastructure.